Romantic turning points and patterns of leaving home: contributions from qualitative research in a southern European country - Nico, M. (2016)
The process and timing of leaving home in Europe has been gaining academic attention the past decades. This is so because this demographic and transitional event provides evidence about the cultural and structural heterogeneity in Europe. Types and timing of conjugality and differences about housing markets, together with cultural contexts and values, are usually given as conjoint causes for the mentioned heterogeneity. But the effects of love-related events in the process and timing of leaving home do not begin or end at conjugal unions. Ruptures, heartbreaks, disputes and conjugal orientations have strong consequences in the trajectories towards adulthood. These effects can only be grasped through qualitative research, capable of giving love and affection the analytical protagonist role they deserve. Only accumulation of comparison-friendly qualitative knowledge on romantic trajectories can allow the study of the heterogeneity of conjugal trajectories. In this research, 52 Portuguese young adults were inquired by biographical interviews and life calendars. Holistic-form analysis provided evidence that the love-related events are significant for changes in the residential trajectories. Five cases were chosen to illustrate the three clusters identified: ‘long relationships and delayed departures’, ‘heartbreaks and breakups, speeding up residential autonomy’ and ‘out of the closet, into a new home’.